Pembuatan Sepeda Air di Kawasan Wisata - Rizwan, Thaib; Chaliluddin; Rizal, Syamsul; Husaini; Thaib, Razali; Muhammad; Zulfahmi, Ilham; Agustina, Imelda; Rahmah, Alvi; Aprilla, Ratna Mutia; Miswar, Edy; Affan, Junaidi M; Setiawan, Ichsan; Prajaputra, Vicky; Rianjuanda; Rahimi, Sayyid Afdhal El (Yayasan Kawanad, 2022)
Water bikes can be used as one of the vehicles in water tourism areas such as Ulee Lheue. Water bikes are used as a medium for surface transportation and fishing. Of course, this can increase the enthusiasm of those who visit the tourist destination of Ulee Lheue on weekends and holidays. High enthusiasm can increase the number of tourists, which increases income and sustains the economy of people around Ulee Lheue. Personal watercraft are constructed using fibrous pins or floats, using propeller drives, and using bicycle frames, usually modified. The steering wheel has a plate at the front and is designed to control the direction of rotation (left and right). A good community economy is expected to deliver the goodness of the community itself. Therefore, watercraft manufacturing activities must be carried out in Ulee Lheue. The implementation of this activity takes place in his two phases of implementing the activity, including creating the water bike design and manufacturing the water bike frame. The existence of water bikes can be used as an alternative to water tourism like Ulee Lheue. Water bikes are used as a medium for surface transportation and fishing. Of course, this can increase the enthusiasm of the community to visit her Ulee Lheue, a tourist destination. In fact, this water he slide is a popular ride for visitors wanting to explore lakes, reservoirs, and artificial ponds.